How ecological, production, and living spaces jointly shape urban spatial integration through resource sharing and interaction - Zhu, Xiangfei; Liu, Yuqi; Zeng, Xiaojun; Yan, Yanqing (Frontiers in Public Health, 2025)
This study focuses on the synergistic integration mechanism of urban Production, Living, and Ecological (P–L–E) spaces, employing a structural equation model (SEM) to elucidate their interaction pathways and the moderating effects of policy implementation and public awareness. Based on 750 survey responses from Guangdong Province, the findings indicate that Perceived Quality of Ecological Space (PQES) exerts the strongest influence on the Degree of Urban Spatial Integration (DUSI; β = 0.236), followed by Production Space Vitality (PSV) and Satisfaction with Living Space (SLS). The key mediating variables—Degree of Shared Access to Spatial Resources (DSSR) and Frequency of Spatial Interaction (FSI)—serve as critical bridges linking the three spatial dimensions to DUSI, with the indirect effect of PQES via FSI being the most pronounced (β = 0.051). Moreover, the Effectiveness of Urban Planning Policy Implementation (EPPI) amplifies the positive impacts of SLS on both resource sharing and interaction frequency, while Public Environmental Awareness (PEA) strengthens the promotive role of ecological space perception in achieving spatial integration. The model explains 43.9% of the variance, unveiling a systematic pathway of “spatial quality enhancement → resource sharing → behavioral interaction → integration achievement.” These findings provide a robust theoretical basis for optimizing the quality of urban production, living, and ecological spaces, as well as for refining policy implementation frameworks. The study underscores the necessity of advancing spatial optimization in tandem with public engagement to build efficient, livable, and sustainable urban spatial systems.